2019
DOI: 10.1097/md.0000000000015024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension among patients aged 50 and older living with human immunodeficiency virus

Abstract: Background: Hypertension is one of the common medical conditions observed among patients aged 50 years and elder living with HIV (EPLWH) and to date no systematic review has estimated its global prevalence. Purpose: To conduct a systematic review to estimate the global prevalence of hypertension among EPLWH. Data Sources: PubMed/MEDLINE, Embase, the Cochrane Library, and Global Health databases for relevant publications up till May 25, 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
6
2
Order By: Relevance
“…The prevalence of NCDs were high and similar to other cohorts of PLWH in the region [12][13][14], with diabetes found in 13%, dyslipidaemia 88% and hypertension 44%. For all three NCDs assessed, a significant proportion of participants were previously undiagnosed and identified only as a result of study screening, implying a poor practice of screening for NCDs as part of routine HIV care (Figure 1).…”
Section: Resultssupporting
confidence: 80%
“…The prevalence of NCDs were high and similar to other cohorts of PLWH in the region [12][13][14], with diabetes found in 13%, dyslipidaemia 88% and hypertension 44%. For all three NCDs assessed, a significant proportion of participants were previously undiagnosed and identified only as a result of study screening, implying a poor practice of screening for NCDs as part of routine HIV care (Figure 1).…”
Section: Resultssupporting
confidence: 80%
“…Researchers in public health as well as clinical streams have long been recognizing the importance of HTN among PLHIV. Plethora of studies have reported data on HTN among PLHIV in different countries and regions across the world [5,[14][15][16][17][18][19][20][21][22][23][24][25][26]. The reports vary from 4.0% to 67.0% by study population, area and time [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This study described the characteristics of EPLHIV in Nigeria; we found a lower prevalence of hypertension in older people on ART in Nigeria as compared to the prevalence of hypertension in sub-Saharan Africa (31.9, 95%CI 18.5-49.2%) and the global prevalence of hypertension (42.0, 95%CI 29.0-55.4%) [25]. Despite the relatively low prevalence of hypertension in older people living with HIV in Nigeria, it is very important for public health experts to deploy preventive interventions that will reduce the occurrence of hypertension.…”
Section: Discussionmentioning
confidence: 75%